IMPLEMENTASI SUPERVISI KEPALA SEKOLAH DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU DI SMPN 2 DIWEK JOMBANG - Nurun Nabilah; Rukhsotun Nu’aimah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
A good teacher will carry out his duties professionally to produce higher quality graduates. This is supported by the role of the principal as a supervisor who has the task of improving teacher pedagogical competence in an effort to create a better learning process through more efficient teaching methods, broad mastery of material which enables students to meet competency standards. This study aims to describe the role of school principals as supervisors in improving the quality of educators, and to describe the pedagogic competence of teachers. This research is a qualitative descriptive study using a case study approach. by observing the role of the principal as a supervisor in improving teacher pedagogical competence at SMPN 2 Diwek Jombang. The subjects of this study were school principals, vice principals for curriculum, teachers and students. The object of this research is the role of the principal as a supervisor in improving teacher pedagogic competence at SMPN 2 Diwek Jombang. This study uses data collection techniques by means of observation, interviews and documentation. Primary data is selected directly from the respondents, while secondary data is in the form of theories from books and journals as well as other supports obtained from school documentation. While testing the validity of the data is done by triangulation of sources. Data analysis in this study used data reduction, data presentation and conclusion. Based on the research results, it can be concluded that the role of the principal as a supervisor in improving the quality of educators has been going well, this is evidenced by the principal making a work program consisting of an annual program and a semester program, the principal also uses techniques in carrying out supervision including are class visit and observation techniques, individual techniques, and group techniques. Meanwhile, the pedagogic competence of teachers at SMPN 2 Diwek Jombang has also been going well. This shows that the teacher has mastered all the core pedagogic competencies of the teacher, but there is still something that needs to be improved, namely regarding reflective action to improve the quality of learning